Gestão dos recursos humanos e gestão de competências-articulação possível?: um estudo comparativo dos serviços de hotelaria hospitalar entre Brasil e Portugal - Daysa Andrade Oliveira (2014)
The aim of this study was to analyze the possible association between human resources and competencies, as far as hospital hotel services are concerned, based on a comparative study between hospitals in Brazil and Portugal. The association among human resources management and competencies enables the alignment of its policies and practices, contributing to the development of organizations, including those of the Health Care industry. This study took an international approach since Brazil and Portugal present similar aspects in culture and economics, considering their peculiarities, and also because there is low demand on researchs regarding human resources in a comparative perspective. The methodological path of this study was taken using a qualitative descriptive research through a multi-case study, being such cases chosen based on an intentional non-probabilistic sample, composed of three hospitals, two from Brazil and one from Portugal, which are so called, for the purpose of this work, Alpha, Beta and Delta. Data were collected through documentary research and semi-structured interviews. A total of 101 workers were interviewed, being 35 of the Human Resources Department and 66 of the Hospital Hotel Services Department. Subsequently, data were analyzed and interpreted using the following dimensions: human resources, human resources management, competencies management, hospital hotel services, hospital hotel services management, association between human resources, competencies and hotel services. The results were correlated to two situations observed in the three cases: a) human resources management is focused on traditional practices, with difficulties to address the competencies ' concept; b) hospital hotel services provide functioning of the hospitals, but their possibilities are notyet fully implemented, once the essential competencies for such services are not taken into account, which would be paramount to improve health care. It was concluded that the hospitals Alpha, Beta and Delta consider individual competencies as preponderant in relation to the organizational competencies, but there is no balance between health care, human resources and hospital hotel services. Therefore, there is no association among human resources and competencies that could influence hospital hotel services. Regardless of whether the hospital is public or private, the logic of association between human resources, skills and competencies does not apply.